Yield line analysis of two way reinforced concrete slabs having different support conditions with opening at any location - Kumar, Navin; Kumar, Veerendra (Journal of Structural Engineering, 2024)
Reinforced concrete rectangular slabs with varying boundary conditions and openings on any location have been analysed using yield line theory. The software developed, based on particular user inputs, is capable of predicting the yield line pattern under the collapse condition with its coordinates as well as able to calculate moments coefficients at collapse. The program developed is for variable size of the opening and for any aspect ratio, thus the limitation of keeping the opening in a particular location and ratio of the dimensions of slabs, have been eliminated. The program developed is best within the limitations of Computer language used and thus the variations in results can be attributed to it.